Anti-Viral Activities Of Centella Asiatica L., Curcuma Longa L. And Strobilanthes Crispus L. Against Pseudorabies Virus In Animal Cell Lines - Hosni, Hanisa (2006)

(untitled)
Herpes simplex virus (HSV) is a major opportunistic pathogen in immunosuppressed patients and a serious disease in high human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome (AIDS) prevalence areas. The existence of resistant strains to the available drug is therefore an urgent need to identify new alternative agents for HSV. The aim of this study is to investigate anti-viral activities of the plants. Assays were developed to determine the characteristics of anti-viral activities, as anti-viral attachment, anti-prophylactic and virucidal. The pseudorabies virus (PrV) has been used as representative of HSV. Three medicinal plants have been used, which is Centella asiatica L. (C. asiatica), Strobilanthes crispus L. (S. crispus) and Curcuma longa L. (C. longa). The plants are reputed in traditional medicine for many treatments of diseases. Firstly, the potential cytotoxicity was evaluated for plant methanol extracts (ME) and aqueous extracts (AE) in cell line by using MTT assay. All three plant extracts were found significantly (P < 0.05) non cytotoxic towards African Green Monkey Kidney (Vero) cells, Baby Hamster Kidney (BHK) cells and Rabbit Kidney (RK) cells. The plant ME was generally more cytotoxic than AE, showed lower (76 μg/ml) non-toxic limit concentration (NTLC50) than plant AE (82 μg/ml). The least cytotoxic was the extract of S. crispus followed by C. asiatica and C. longa. The resistance of three different cell lines was also compared and it showed the BHK cells were the most toughest and resistant to the plant extracts. In anti-viral analysis, it was discovered that all plant extracts showed marked prophylactic activity, considerable anti-attachment and virucidal abilities up to 75% inhibition of cytopathic effect (CPE) formation. The C. longa extract was found as a potent anti-viral agent followed by S. crispus and C. asiatica. It exerted better prophylactic activity against PrV compared to the other two plants. Whereas S. crispus was found very effective as virucidal agent while C. asiatica as anti-viral attachment agent. Based on the results, it was also found that plant ME possessed better anti-viral activity than plant AE. These results also showed each of three plants possessed different anti-viral activities. The anti-viral activities were also varies in different cell lines tested. All three plants were analysed by liquid chromatography-electrospray ionisation-mass spectrometry (LC-ESI-MS) to identify plant compounds. The analysis revealed several compounds in C. asiatica, S. crispus and C. longa ME. This study discovered the promising anti-viral activities of C. asiatica, S. crispus and C. longa but not any identified plant compound against PrV in vitro. These results suggest that all three plant extracts have potent anti-viral agents against PrV as representative of HSV that can be exploited for development of an alternative medicine to prevent HSV infections.